Resilience and Transformation: Analysis of the Mexican Economy in Times of Pandemic and Post-Pandemic - Chiatchoua, Cesaire; Betancourt, Ernest Yasser Nuñez; Gaitan, Carlos Ernesto Luquez (Journal of Posthumanism, 2025)
The emergence of the pandemic has surprised the world, generating a significant impact on macroeconomic variables and impacting the quality of life of citizens. The objective of this research is to analyze economic performance in the pandemic and post-pandemic scenario through the use of segmented regression models in order to formulate political strategies that contribute to improving the living conditions of the citizens of Mexico. Using data from February 2020 to March 2023, it was found that, in the first period, a significant and positive correlation ( r=0.9026622) between confirmed cases of COVID-19 and deaths. In the second period, only the IGAE showed a significant relationship with confirmed cases and deaths. From the above, the need arises to strengthen the mechanisms and programs for access to regulated credit for micro and small businesses, access to social security, access to public health services, as well as the incorporation of women into the formal labor market.